Identification and Biosynthesis of Fibrinogen in Human Uterine Cervix Carcinoma Cells - Young Lee, Soo; Pyoung Lee, Key; Weon Lim, Joo (Thrombosis and Haemostasis, 1996)
Fibrinogen has been detected in ME-180 human uterine cervix carcinoma cells, and synthesis of fibrinogen by ME-180 cells has been measured using [35S] L-methionine incorporation. Expression of mRNA for the B|3-chain of the fibrinogen in ME-180 cells has been identified by PCR-assisted mRNA amplification. The AΑ-, BΒ-, and Γ-chains of fibrinogen synthesized by ME-180 cells were chemically and immunologically identical to those of plasma fibrinogen. These findings suggest that fibrinogen is present and synthesized in ME-180 human uterine cervix carcinoma cells, and that fibrinogen plays a role in these malignant tumor cells.